Connecting amanah (trustworthiness) with employee engagement: does it matter in Islamic higher education institutions in Malaysia? - Jaiyeoba, Haruna Babatunde; Hazahari, Noor Yuslida; Hussein, Ahmad Sallehin (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia (IIUM), 2021)
This study aims to ascertain whether Amanah is crucial for employee engagement in Islamic higher education institutions in Malaysia. To this end, this study adopts a quantitative research design. Along this line, a questionnaire was developed and used to collect data from 345 employees who are currently working with Islamic higher education institutions in Malaysia. The data received was analysed using descriptive analyses and it was discovered that Amanah is considered as an important concept for employee engagement in Islamic higher education institutions in Malaysia. Hence, emphasising Amanah by the management of Islamic higher education institutions in Malaysia will assist employees in getting themselves engaged. As such, future studies should consider including Amanah with other variables when investigating employee engagement, especially in Islamic higher education institutions.